Optimalisasi Fungsi-Fungsi Jabatan Kepemimpinan Gerejawi sebagai Salah Satu Perwujudan Pelayanan yang Holistik - Bakhoh Jatmiko (SANCTUM DOMINE: JURNAL TEOLOGI, 2019)
God has established His church on the earth purposefully. One of God’s purposes in establishing His chruch is that the church can provide the answers for the very complex needs of this earth. This research is being conducted in order to discover the biblical model of the church’s ministries wholelistically using the roles and function of church leadership that are mentioned in the New Testament. The approach methode that is being used in this research, is exploring New Testament texts related to leadership role in the early church. The early Christian church was equiped with the roles of appostle, deacon and elder, each with their own responsibilities that complement each other in order to create wholistic ministry in the church.